If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7n + -3 = 27 + 2n Reorder the terms: -3 + 7n = 27 + 2n Solving -3 + 7n = 27 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. -3 + 7n + -2n = 27 + 2n + -2n Combine like terms: 7n + -2n = 5n -3 + 5n = 27 + 2n + -2n Combine like terms: 2n + -2n = 0 -3 + 5n = 27 + 0 -3 + 5n = 27 Add '3' to each side of the equation. -3 + 3 + 5n = 27 + 3 Combine like terms: -3 + 3 = 0 0 + 5n = 27 + 3 5n = 27 + 3 Combine like terms: 27 + 3 = 30 5n = 30 Divide each side by '5'. n = 6 Simplifying n = 6
| 3=.2x-7 | | (56)34g*4568284792638718462677488=537g*34 | | -(3x+4)=x-16 | | 5x-6y=64 | | 160+80+x=180 | | 7+2x=2(x-1)+4 | | 5x-12=-2+5(x-2) | | 24x+36x+108x= | | 7387178g*71893=g/783878278672614460 | | 8x+4=9+4(2x-1) | | -7e-3= | | 8y-3=20y+93 | | 2s^2+7s+6=0 | | 13*2-10= | | [4-(-49)]= | | 2x-(180-x)=27 | | 168.2=i^2(20) | | y(5y)=2000 | | 3t+19=-10 | | 10x-4=4x+1 | | 2t^8(t-t+7t^3)= | | -2+8=-22+6 | | s=1809(n-2) | | (x-2)(x+2)=12(5) | | 10-4y=-50 | | 210-w=142 | | -(7x-4y-9)= | | 21+-x=245 | | 5(3y-9)-(5y+4)= | | 5x=-6+7x | | x=2(90-x)-12 | | 97-w=170 |